Object-Oriented Modelling Of Kerberos Based Authentication Process In E-Banking Transaction - Nath, M. Das; Karforma, S (International Journal of Computer Sciences and Engineering, 2025)
The exponential growth and the success rate of different electronic application areas like E-Services, EGovernance, E-Payment, E-Banking, E-Shopping etc is enormously dependant on security, authenticity and integrity of the most confidential information which is sent across the network by the sender. With the increasing menace of several cyber threats, the sender has to feel safe in sending across their identity details over the communication medium. On the other hand, the receiver must receive the same, without any loss or tampering of information as there are several intruders or eavesdroppers waiting to steal the financial data/information. The security parameters cannot be compromised at any cost. Hence, to combat the pilferage of data, different types of authentication protocols and mechanisms have been in use. For example, the banking sector often uses a two-factor authentication, e-commerce merchants go for different layers of authentication and so on. This paper focuses on the use of the most popular authentication protocol, Kerberos, which could be applied for logging in for ebanking system, in order to achieve the highest level of security. Furthermore, we have tried an attempt to use object-oriented modeling to show the working of the authentication with the help of Kerberos and IDEA encryption algorithm as an added level of protection